2002
DOI: 10.1300/j013v35n04_03
|View full text |Cite
|
Sign up to set email alerts
|

Female Garment Factory Workers in Cambodia: Migration, Sex Work and HIV/AIDS

Abstract: Female garment factory workers in Cambodia are more exposed to HIV/AIDS than previously thought. Although HIV/AIDS epidemics are fast spreading in Cambodia, relatively little is known about the sexual health of women other than those perceived as commercial sex workers or married women of reproductive age. In-depth interviews with 20 unmarried female garment factory workers, who reported to have engaged in multi-partnered sex through direct or discretionary commercial sex occupations, demonstrate that they are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
43
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 2 publications
6
43
0
Order By: Relevance
“…Yet recent research conducted across distinct socio-cultural contexts has found that female sex workers often have a variety of paying partner types that range in levels of perceived relationship intimacy. Such studies have found that condom use rates among sex workers and their paying partners vary based on whether these relationships are regular versus casual in nature (Kerrigan, Moreno, Rosario, & Sweat, 2001;Mgalla & Pool 1997;Nishigaya, 2002;Outwater et al, 2000;Pickering, Quigley, Hayes, Todd, & Wilkins, 1993;Wawer, Podhisita, Kanungsukkasem, Pramualratana, & McNamara, 1996). These studies suggest that even within the context of commercial sex, relationship intimacy may be a key determinant of unprotected sex between sex workers and their regular paying partners.…”
Section: Introductionmentioning
confidence: 98%
“…Yet recent research conducted across distinct socio-cultural contexts has found that female sex workers often have a variety of paying partner types that range in levels of perceived relationship intimacy. Such studies have found that condom use rates among sex workers and their paying partners vary based on whether these relationships are regular versus casual in nature (Kerrigan, Moreno, Rosario, & Sweat, 2001;Mgalla & Pool 1997;Nishigaya, 2002;Outwater et al, 2000;Pickering, Quigley, Hayes, Todd, & Wilkins, 1993;Wawer, Podhisita, Kanungsukkasem, Pramualratana, & McNamara, 1996). These studies suggest that even within the context of commercial sex, relationship intimacy may be a key determinant of unprotected sex between sex workers and their regular paying partners.…”
Section: Introductionmentioning
confidence: 98%
“…In a wide search of multiple databases (CINAHL, Embase, Medline, Psychinfo, Genderwatch, Women's Studies International, eHRAF Collection of Ethnography and Sociologic Abstracts) using the key words "Cambodia", "migration", and "HIV", only a single study on garment factory workers was found (Nishigaya, 2002). Beyond this, there are a limited number of studies published elsewhere and in the grey literature.…”
Section: Cambodian Literature On Migrant Womenmentioning
confidence: 99%
“…The paucity of research on this population is strong rationale for the importance of this research. Nishigaya (2002) described the findings of interviews with twenty garment factory workers who supplemented their income by work in the sex trade. She explored the women"s reasons for engaging in sex work, their working conditions in the sex industry, their "sweetheart" relationships, and their partners" use of condoms.…”
Section: Cambodian Literature On Migrant Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…Poverty drives a level of complicity with poor rural families, who receive financial incentives to entrust their girls to agents in return for false assurances of work as cooks, maids, waitresses and factory workers. 49 The direct links to poor education, child labour and poverty are broadly reported, 50,51 with migration from remote areas to Phnom Penh in order to find employment seen as part of the journey towards sexual exploitation. 52 An almost inevitable association between sexual exploitation and Western tourism is drawn:…”
mentioning
confidence: 99%